К классификационной и характерологической типологии проявлений языковой материи (На материале курдского языка) - Хамоян, Максим («Զանգակ - 97»)
The ariicle conlains malerial on classification and characterologic typology of thelinguislic matter manifestation. It illustrates the nature of the phenomena and theirl linguistic assignment in the language system.
Keywords: Филология; Лингвистика